Review of Chirothrips and related genera (Thysanoptera: Thripidae) of the Americas, with descriptions of one new genus and four new species - Nakahara, Sueo; Foottit, Robert G. (Zootaxa, 2012)
The species of Chirothrips and related genera occurring in the Americas are reviewed. Seventeen species from the areaare retained in Chirothrips, 15 species are treated in Arorathrips, two species in Konothrips, one species in Oelschlaegeraand one species in the new genus Unilobothrips. The generic concepts of the four previously described genera are revised.Four new species, Arorathrips childersi, Chirothrips hemingi, Konothrips colei, and Unilobothrips cornuatus are de-scribed. Chirothrips moultoni Post is synomymized with C. aculeatus Bagnall, and C. spinosus Moulton with Arorathripstexanus (Andre). The following new combinations are proposed: Arorathrips crassus (Hinds), A. crenulatus (Hood), A.dorsalis (Hood), A. lenape (Hood), A. oneillae (Watts), A. sericatus (Hood), A. texanus (Andre), A. vestis (Hood) and Oel-schlaegeria priesneri (Hood) (all from Chirothrips). Chirothrips mongolicus zur Strassen is returned to Chirothrips from Arorathrips. Identification keys to genera and species, and known distributions of the species, are provided.